Pengolahan Limbah Produksi Usaha Mikro, Kecil, dan Menengah Menjadi Kerajinan Kreatif - Riswanda Himawan; Riefda Arya Kelana; Ajeng Retno Ariani; Piska Eka Widya (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2022)
Micro, small and medium enterprises (MSMEs) are community associations that carry out entrepreneurial activities closely related to the economic field. Through MSMEs, it is easier for people to collaborate with one another. One of the villages that strongly supports the development of SMEs is Gilangharjo Village. The great numbers of local MSME actors in the culinary field have greatly advanced the village economy. However, almost every day these MSME actors produce various kinds of waste from merchandise production. These problems can actually be handled by processing waste into creative crafts with economic value. The purpose of the service program is to increase the economic value of waste as an additional income for MSME actors. The socialization, training, and marketing assistance were coducted to assist them. The results of the program show that MSME waste can be processed into trinkets in Gilangharjo Village, and potentially increase the income of MSMEs in Gilangharjo Village.